2000
DOI: 10.1117/12.406584
|View full text |Cite
|
Sign up to set email alerts
|

JPEG-2000 compression using 3D wavelets and KLT with application to HYDICE data

Abstract: JPEG-2000 is the new image compression standard currently under development by ISOIIEC. Part I of this standard provides a "baseline" compression technology appropriate for grayscale and color imagery. Part II of the standard will provide extensions that allow for more advanced coding options, including the compression of multiple component imagery. Several different multiple component compression techniques are currently being investigated for inclusion in the JPEG-2000 standard. In this paper we apply some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…This data was collected from an airborne platform at an altitude of 1.5 km; at this altitude, the ground sample distance is approximately 0.8 m. The HYDICE sensor returns data as 12-bit unsigned integers. However, calibration increases the dynamic range and occasionally produces negative values [ 13]; hence, the radiance values are stored as 16-bit signed integers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This data was collected from an airborne platform at an altitude of 1.5 km; at this altitude, the ground sample distance is approximately 0.8 m. The HYDICE sensor returns data as 12-bit unsigned integers. However, calibration increases the dynamic range and occasionally produces negative values [ 13]; hence, the radiance values are stored as 16-bit signed integers.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting principal-component images (PC images) are then compressed spatially and independently using the JPEG2000 standard. Other researchers [23,13,24,20] have implemented similar schemes. In this section, we elaborate on the main parts of the scheme, which is diagrammed in Figure 3.…”
Section: Compression Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The only studies to date on the exploitability of lossily compressed and reconstructed hyperspectral imagery, however, are quite recent and few in number. The papers by Brower et al [3] and Kasner et al [6] compared different combinations of JPEG-2000 options on hyperspectral imagery in terms of root mean-square error or peak signal to noise ratio. In Shen and Kasner [10], the authors studied anomaly detection and material identification tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], it is shown that the best option to perform a 3-dimensional DWT is the hybrid transform, which consists of applying first the DWT in the spectral domain followed by a two dimensional squared DWT. In [9,10,11,7], it is demonstrated that, as a spectral decorrelator, PCA provides better performance than DWT (around 5dB). Recent works [12,13] indicate that there exist anomalous pixels, and if they are detected, the performance of the coder can be further improved using the PCA.…”
Section: Introductionmentioning
confidence: 99%